Rancang Bangun Sistem Informasi Distrik Masni Berbasis Web Menggunakan Framework Codeigniter 3: Web-Based Masni District Information System Design Using Codeigniter 3 Framework - Muhammad Zamachsyari; Lion Ferdinand Marini; Christian Dwi Suhendra (JISTECH: Journal of Information Science and Technology, 2024)
This research discusses designing a website-based information system using the CodeIgniter Framework. The aim of this research is to optimize district information management, increase open access to information for the community, and speed up the data management process at the district level. The research methodology involves requirements analysis, system design, implementation using CodeIgniter, and system performance evaluation. A needs analysis is carried out to identify the information needed by the community, district government and other related parties. With the results of this analysis, system design was carried out by utilizing the features provided by the CodeIgniter Framework, such as model-view-controller (MVC) to separate application logic and display. CodeIgniter's advantages in database management and ease of web application development are the main focus in developing this system. The user interface is designed to be responsive and easy for users to use. Designing a website-based district information system using the CodeIgniter Framework can make a positive contribution in increasing the efficiency of district information management, providing better accessibility to the community, and supporting transparency and accountability of district governments in data and information management.